2009
DOI: 10.1007/s11069-009-9416-x
|View full text |Cite
|
Sign up to set email alerts
|

Tornado fatalities and mobile homes in the United States

Abstract: Fatalities from tornadoes have declined dramatically over the last century in the United States. Despite the overall reduction in tornado lethality, fatalities from mobile homes remain high. In fact, research suggests that the likelihood of a fatality in a mobile home is ten times or more than that in a permanent home. This study examines possible explanations of the mobile home tornado problem, including the potential for concentration of these homes in tornado prone states, the relation to Fujita Scale ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 16 publications
(22 reference statements)
4
36
0
Order By: Relevance
“…Tornado fatalities in the United States have been studied over time, by month, by time of day and the day of week, by state/region, by F scale or EF scale rating, by lead time, by place or location of death, by age and sex of the deceased, and so forth (e.g., Daley et al 2005;Ashley 2007;Wurman et al 2007;Simmons and Sutter 2008;Sutter and Simmons 2010;Sutter 2011, 2012;Simmons et al 2012). Simmons and Sutter (2011) have identified four major vulnerabilities for tornado casualties: tornadoes that occur overnight, tornados that occur during the fall/winter months, residence in a mobile home, and location in the United States (specifically, the southeastern part of the United States; see also Schmidlin et al 2009;Chaney and Weaver 2010).…”
Section: Tornado Fatalities: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tornado fatalities in the United States have been studied over time, by month, by time of day and the day of week, by state/region, by F scale or EF scale rating, by lead time, by place or location of death, by age and sex of the deceased, and so forth (e.g., Daley et al 2005;Ashley 2007;Wurman et al 2007;Simmons and Sutter 2008;Sutter and Simmons 2010;Sutter 2011, 2012;Simmons et al 2012). Simmons and Sutter (2011) have identified four major vulnerabilities for tornado casualties: tornadoes that occur overnight, tornados that occur during the fall/winter months, residence in a mobile home, and location in the United States (specifically, the southeastern part of the United States; see also Schmidlin et al 2009;Chaney and Weaver 2010).…”
Section: Tornado Fatalities: An Overviewmentioning
confidence: 99%
“…7 Sutter and Simmons (2010) reported that more fatalities occur in mobile homes in less powerful tornadoes-those rated EF1, EF2, or EF3 on the EF scale-than fatalities overall. More specifically, EF1 and EF2 tornadoes are potentially lethal for residents of mobile homes.…”
Section: Location Of Deathmentioning
confidence: 99%
“…In terms of housing type, the most vulnerable populations are those living in mobile homes (Brooks and Doswell 2002;Sutter 2005, 2008a;Ashley 2007;Sutter and Simmons 2009;Chaney and Weaver 2010). Timing of the storm can increase vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the cry-wolf effect is not fully known and Barnes et al (2007) found that an isolated false alarm may not be detrimental to warning response. Simmons and Sutter (2009) found that local, recent false alarms increased tornado fatalities and injuries. A one standard deviation increase in the false alarm ratio increased expected fatalities 12%-29% and expected injuries 13%-32% (Simmons and Sutter 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation